Candida tropicalis defibrillator endocarditis: A case report and review of current literature - Bauer, Bastian Klemens (Med Mycol Case Rep, 2019)
We provide a review of current literature and report on a case of electronic device infective endocarditis with C. tropicalis. A 64-year-old man presented for revision of his implantable cardioverter defibrillator. Echocardiography revealed extensive vegetations attached to the Eustachian valve and in the right ventricular apex. Microbiological findings presented C. tropicalis on the explanted material. The patient refused additional surgical intervention. We successfully treated the patient with liposomal Amphotericin B and Flucytosine for 8 weeks.